Mitophagy in Parkinson’s Disease: Pathogenic and Therapeutic Implications - Gao, Fei; Yang, Jia; Wang, Dongdong; Li, Chao; Fu, Yi; Wang, Huaishan; He, Wei; Zhang, Jianmin (Frontiers in Neurology, 2017)
Neurons affected in Parkinson’s disease (PD) experience mitochondrial dysfunction and bioenergetic deficits that occur early and promote the disease-related α-synucleinopathy. Emerging findings suggest that the autophagy-lysosome pathway, which removes damaged mitochondria (mitophagy), is also compromised in PD and results in the accumulation of dysfunctional mitochondria. Studies using genetic and toxin-induced animal and cellular models as well as postmortem human tissue indicate that impaired mitophagy might play a critical role in the pathogenesis of synaptic dysfunction and the aggregation of misfolded proteins, which in turn impairs mitochondrial homeostasis. Interventions that stimulate mitophagy to maintain mitochondrial health might therefore be used as an approach to delay the neurodegenerative processes in PD.